Temuan Pengawasan Bawaslu Terhadap Tidak Netralitasnya Kpu Dalam Tahapan Pemilu 2024 (Studi di Bawaslu Kalimantan Selatan) - Limbong, Jaya Hasiholan; Romdoni, Muhamad (Fakultas Hukum Universitas Primagraha, 2024)
The KPU has the authority to formulate regulations the stages of the election. The KPU's significant authority is prone abuse, such as allegations of fraud committed by the KPU which lead to non-neutrality. As for the issue being raised, What are the supervisory actions of Bawaslu in South Kalimantan regarding the condition of the KPU not being neutral? What is attitude of the Bawaslu in Kalimantan Selatan regarding the alleged abuse of KPU authority in the 2024 Pilkada? This study compiled using normative juridical research methods with empirical data. The results showed Bawaslu in Kalimantan Selatan carried out systematic surveillance with ad-hoc findings by KPU members who were caught red-handed forging signatures. Bawaslu in Kalimantan Selatan has formed 157 Standby Pos Siaga in event of fraud. Supervision is carried out that KPU remains neutral carrying out its duties. Suggestions to KPU to carry out technical guidance intensively eliminate abuse of authority.